Discovery of an [Fe/H] ∼ −4.8 Star in Gaia XP Spectra - Guilherme Limberg; Vinicius M. Placco; Alexander P. Ji; Yupeng Yao; Anirudh Chiti; Mohammad K. Mardini; Anna Frebel; Silvia Rossi (The Astrophysical Journal Letters)
We report on the discovery of GDR3_526285 (Gaia DR3 Source ID 5262850721755411072), a star with [Fe/H] = −4.82 ± 0.25 and one of the lowest metal (atomic number > 2) mass fractions ever found ( Z _GDR3 _ _526585 ≲ 1.0 × 10 ^−6 ). We first identified it as an ultra-metal-poor (UMP; [Fe/H] < −4) red-giant branch (RGB) star candidate in the Gaia Blue (BP) and Red (RP) Photometer (XP) spectrophotometric catalog (Gaia G magnitude ≈ 15). A combination of multiband photometry and high-resolution spectroscopic analysis under local thermodynamic equilibrium confirmed the status of GDR3_526285 as a distant (≈24 kpc from the Sun) RGB star ( T _eff = 4596 K, ${log}\,g=0.88$ ) in the Milky Way’s outer halo. We obtain only an upper limit for the carbon abundance of [C/H] < −4.32, resulting in [C/Fe] < +0.50. A correction for the evolutionary carbon depletion (Δ[C/Fe] = +0.68) brings the nominal carbon-to-iron ratio upper limit to [C/Fe] _cor < +1.18. Given its extraordinarily low [C/H], GDR3_526285 likely formed from gas cooled via dust grains rather than fine structure line cooling. The kinematics of GDR3_526285 suggests that this star was either dynamically perturbed by the infall of the Magellanic system or was formerly a member of the Magellanic Clouds and was later stripped by the Milky Way. Our results showcase the potential of an all-sky search for low-metallicity targets with Gaia XP and confirm that the methodology described here is a useful “treasure map” for finding additional UMP stars.